Structuration et trajectoires idéologiques des partis catalanistes et nationalistes catalans depuis la Transition - Alicia Fernández García; Mathieu Petithomme (Cahiers de Civilisation Espagnole Contemporaine)
This article traces the structuring and the ideological trajectories of catalanist and nationalist parties in Catalonia since the transition to democracy. It first presents the evolution of the political relationships in Catalonia and the role of Catalanism on the Spanish political scene. Then, through an empirical analysis of the party manifestoes of ERC, CiU, the PSC and the PSUC-ICV, it apprehends the plurality and the nuances of the Catalan nationalist ideologies and of catalanist political discourses. More precisely, the article defines the convergences and the cleavages between these four political groups on the questions of the Catalan language, on the objectives and the means of Catalan nationalism, and on the relationships to develop with the Spanish state. Finally, it concludes on the controversy around the 2006 status of autonomy, and the more recent restructuration of the Catalan party system around the question of the future referendum of independence.